PENGARUH FIRM SIZE, GROWTH PPORTUNITY, DAN LEVERAGE TERHADAP FIRM VALUE MELALUI CASH HOLDING SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SUB SEKTOR PERKEBUNAN YANG TERDAFTAR DI BEI TAHUN 2019-2022 - Inggriani, Desi; Arief, Mohammad Yahya; Minullah, Minullah (Fakultas Ekonomi dan Bisnis, 2024)
Technological advances have fundamentally changed the business landscape and revolutionized entrepreneurial practices. In order to expand the business they own, entrepreneurs must not only pay attention to assets and profits, but also company values ​​must be built. Currently, firm size is no longer measured based on profits or assets, but also on company value. The aim of this research is to see the influence of Firm size, Growth opportunity, and Leverage on Firm value through Cash holding. This research is quantitative research. The population in this research is 32 plantation sub-sector companies registered on the IDX in 2019-2022. The samples were selected using the purposive sampling method and a sample of 8 companies was obtained. Data analysis and hypothesis testing were carried out using the structural equation model-Partial Least Square (PLS). The results of the direct influence hypothesis test using the Smart PLS 3.9 application, show that Firm size has a significant negative effect on Cash holding, Growth opportunity has a positive but not significant effect on Cash holding, Leverage has a negative but not significant effect on Cash holding, Firm size has a significant negative effect on Firm value, Growth opportunity has a negative but not significant effect on Firm value, Leverage has a positive but not significant effect on Firm value, Cash holding has a significant negative effect on Firm value. The results of the indirect influence hypothesis test show that the variable Firm size on Firm value through Cash holding has a positive but not significant effect, Growth opportunity on Firm value through Cash holding has a negative but not significant effect, Leverage on Firm value through Cash holding has a positive but not significant effect.